Differential profiles of adverse events associated with mycophenolate mofetil between adult and pediatric renal transplant patients. Issue 11 (November 2018) - Hosohata, Keiko; Matsuoka, Etsuko; Inada, Ayaka; Oyama, Saki; Niinomi, Iku; Mori, Yasuhiro; Yamaguchi, Yuki; Uchida, Mayako; Iwanaga, Kazunori
Objective: Immunosuppressive regimens after renal transplantation usually include a combination of calcineurin inhibitors, corticosteroids, and a proliferation inhibitor, either azathioprine or mycophenolate mofetil (MMF), to prevent rejection and maintain graft function. MMF has a stronger immunosuppressive effect than does azathioprine. This study aimed to examine MMF-associated adverse events in renal transplant patients. Methods: Retrospective pharmacovigilance disproportionality analysis was conducted using the Japanese Adverse Drug Event Report database. Results: A total of 11, 594 adverse drug events were reported in renal transplant patients; 10, 272 (88.6%) involved adults and 1322 (11.4%) involved children. In adult patients, the most frequent adverse events induced by MMF were cytomegalovirus infection (272 reports), urinary tract infection (69 reports), and polyomavirus-associated nephropathy (61 reports). Among adverse events, the highest reporting odds ratio (ROR) was found for cytomegalovirus infection (ROR, 1.58; 95% confidence interval, 1.36–1.83). In pediatric patients, the rank order for MMF-associated adverse events was cytomegalovirus infection (27 reports), bronchitis (23 reports), and cytomegalovirus viremia (19 reports), but these adverse events were not detected as a signal. Conclusion: Our results show the safety profile of MMF in pediatric renal transplant patients. These findings can be used to update information used for prescriptions for pediatric patients.